International Conference on Advancements of Medicine and Health Care through Technology; 12th - 15th October 2016, Cluj-Napoca, Romania MEDITECH 2016 - Vlad, Simona; Roman, Nicolae Marius; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This volume presents the contributions of the fifth International Conference on Advancements of Medicine and Health Care through Technology (Meditech 2016), held in in Cluj-Napoka, Romania. The papers of this Proceedings volume present new developments in - Health Care Technology, - Medical Devices, Measurement and Instrumentation, - Medical Imaging, Image and Signal Processing, - Modeling and Simulation, - Molecular Bioengineering, - Biomechanics.
Health Care Technology -- Medical Devices, Measurement and Instrumentation -- Medical Imaging, Image and Signal Processing -- Modelling and Simulation -- Molecular Bioengineering, Biomechanics.
Keywords: Biomedical engineering; Medicine -- Research; Biology -- Research; Signal processing; Public health; Biomedical Engineering and Bioengineering; Biomedical Research; Signal, Speech and Image Processing; Public Health